Antara Spiritualitas Tarekat dan Tradisi Mandailing: Identitas Khas Parsulukan Babul Falah - Daulay, Romaito; Arifin, Zainal; Delfi, Maskota (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This paper examines the existence of Parsulukan Babul Falah in Simaninggir Village as a spiritual center that survives amidst the current of modernization. The purpose of this paper is to understand the background of the interest of outsiders in the activities of the tarekat and to identify the unique cultural identities and values that have developed within it. This paper uses a descriptive qualitative method with an ethnographic approach through observation, interviews, and literature studies. The author involved 10 informants from various circles, including murshid, congregation, caliph of parsulukan, and the local community. The results show that the main attraction of Parsulukan Babul Falah lies in the combination of two major tarekats, namely Naqsabandiyah and Sammaniyah, which provide a profound spiritual experience through the practice of suluk, zikir khafi, and regular religious studies. Parsulukan Babul Falah has seven unique identities that distinguish it from other tarekat centers and make it popular in Mandailing Natal. The identity includes the lineage of scholars, the role of the mursyid in treating people, the certificate of the lineage of Sheikh H. Arifin Hasibuan as a caliph, religious studies every Monday, the tradition of aek tawajuh, language adjustments by the mursyid and the principle of no change in teachings. This paper provides an important contribution in understanding the relationship between the tarekat, local culture and collective identity in the context of the Islam of the Mandailing Natal community.